2020
DOI: 10.1002/anie.202004354
|View full text |Cite
|
Sign up to set email alerts
|

Isothiourea‐Catalyzed Acylative Kinetic Resolution of Tertiary α‐Hydroxy Esters

Abstract: A highly enantioselective isothiourea‐catalyzed acylative kinetic resolution (KR) of acyclic tertiary alcohols has been developed. Selectivity factors of up to 200 were achieved for the KR of tertiary alcohols bearing an adjacent ester substituent, with both reaction conversion and enantioselectivity found to be sensitive to the steric and electronic environment at the stereogenic tertiary carbinol centre. For more sterically congested alcohols, the use of a recently‐developed isoselenourea catalyst was optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 97 publications
(24 reference statements)
0
59
0
Order By: Relevance
“…BTM ( ITU 1 [ 33 ]) and HyperBTM ( ITU 2 [ 38 ]) are amongst the most commonly used chiral ITUs and these nowadays commercially available catalysts were used to optimize the resolution of rac - 2 with isobutyric anhydride ( 4a ) ( Table 1 gives an overview of the most significant results obtained in this screening). Anhydride 4a was chosen in a first instance as it proved successful in previous acylative resolutions reported by others [ 28 , 33 34 36 37 ] but we later on also tested other anhydrides and acid chlorides (vide infra, Scheme 2 ). First experiments with 10 mol % BTM ( ITU 1 ) carried out in CHCl 3 or toluene at room temperature ( Table 1 , entries 1 and 2) proved the general feasibility of this concept, resulting in s -factors around 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BTM ( ITU 1 [ 33 ]) and HyperBTM ( ITU 2 [ 38 ]) are amongst the most commonly used chiral ITUs and these nowadays commercially available catalysts were used to optimize the resolution of rac - 2 with isobutyric anhydride ( 4a ) ( Table 1 gives an overview of the most significant results obtained in this screening). Anhydride 4a was chosen in a first instance as it proved successful in previous acylative resolutions reported by others [ 28 , 33 34 36 37 ] but we later on also tested other anhydrides and acid chlorides (vide infra, Scheme 2 ). First experiments with 10 mol % BTM ( ITU 1 ) carried out in CHCl 3 or toluene at room temperature ( Table 1 , entries 1 and 2) proved the general feasibility of this concept, resulting in s -factors around 6.…”
Section: Resultsmentioning
confidence: 99%
“…With these optimum conditions the resolution was also successfully carried out on 1 mmol scale, resulting in an identical conversion and s -factor ( s = 20; C = 57%) and allowing for the isolation of ( R p )- 2 in 39% yield (94% ee) and ( S p )- 3a in 53% yield (71% ee) ( Table 1 , entry 11). Mechanistically, this resolution process should proceed via the well-understood formation of a chiral acyl-transfer species between the isothiourea catalyst ITU 2 and the anhydride 4a [ 33 37 ], which then allows for the resolution of the enantiomers of alcohol 2 . Unfortunately, however, the true nature of this enantiodiscriminating step has not yet been elucidated and will require detailed computational studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BTM (ITU 1 [33]) and HyperBTM (ITU 2 [38]) are amongst the most commonly used chiral ITUs and these nowadays commercially available catalysts were used to optimized the resolution of rac-2 with isobutyric anhydride (4a) ( Table 1 gives an overview of the most significant results obtained in this screening). Anhydride 4a was chosen in a first instance as it proved successful in previous acylative resolutions reported by others [28,33,34,36,37] but we later on also tested other anhydrides and acid chlorides (vide infra, Scheme 2). concentration at -40 °C next showed that toluene allows for higher selectivities than CHCl3 (compare entries 6 and 7), while the use of other solvents like CH2Cl2 and THF resulted in almost no product formation and no reasonable selectivities (not mentioned in the table).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the interest in compound 2, we thus thought about developing an alternative organocatalytic kinetic resolution protocol to control the esterification of rac-2. Chiral isothioureas (ITUs) emerged as easily available and powerful catalysts for numerous applications [29][30][31][32] and have been very successfully used for the kinetic resolution of different racemic alcohols [33][34][35][36][37]. Inspired by this unique catalysis potential, we therefore became interested in testing those chiral catalysts for the, to the best of our knowledge, so far not investigated acylative kinetic resolution of 4hydroxy[2.2]paracyclophane 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%